2022
DOI: 10.51620/0869-2084-2022-67-3-163-169
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of oral cavity patients with periodontitis, adhesive and biofilm forming properties

Abstract: The work characterizes the intestinal microbiota of patients with ischemic stroke, including the spectrum, frequency and number of microorganisms, as well as the spectrum and amount of gas signaling molecules secreted by lactobacilli. It was found that in patients with ischemic stroke, the frequency of the main representatives of normal microflora, Bifidobacterium spp., Lactobacillus spp., Escherichia coli, decreased in 2-3 times, and the same time the prevalence of Clostridia spp., Bacillus spp., Peptostrepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies have shown that Peptostreptococcus was positively correlated with the cardiometabolic biomarker high-sensitivity C-reactive protein, which was involved in the cardiovascular diseases ( 24 , 24 ). Furthermore, as a potential mediator of microbiome ecological dysregulation, Peptostreptococcus is enriched in the gut microbiota of patients with autoimmune diseases and ischemic stroke ( 25 , 26 ). Gemella is also a part of the human oral microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Peptostreptococcus was positively correlated with the cardiometabolic biomarker high-sensitivity C-reactive protein, which was involved in the cardiovascular diseases ( 24 , 24 ). Furthermore, as a potential mediator of microbiome ecological dysregulation, Peptostreptococcus is enriched in the gut microbiota of patients with autoimmune diseases and ischemic stroke ( 25 , 26 ). Gemella is also a part of the human oral microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Peptostreptococcus was positively correlated with the cardiometabolic biomarker high-sensitivity C-reactive protein, which was involved in the cardiovascular diseases [22]. Furthermore, as a potential mediator of microbiome ecological dysregulation, Peptostreptococcu is enriched in the gut microbiota of patients with autoimmune diseases and ischemic stroke [23]. Gemella is also a part of the human oral microbiome.…”
Section: Discussionmentioning
confidence: 99%